PROFIL BERPIKIR KREATIF SISWA DALAM MENYELESAIKAN SOAL SEGIEMPAT DAN SEGITIGA - Setiawan, Toto Bara; Octafia, Yuni; Sunardi, S (Department of Mathematics Education , University of Jember, 2018)
This qualitative reasearch aims to describe on creative thinking of student of SMPN 3 Jember class VIII-D in solving the sum of rectangle and triangle. The subjects consisted of 6 students from class VIII-D 6/2, each students had a high (SK1 and SK2), medium (SK3 and SK4), and low (SK5 and SK6) math skills. Data is collected by test and interview. The result of this research shows that creative thingking of student have been in four indicators, those are fluency, flexibility,originality,and elaboration. This research show that in preparation stage, SK1 belong to TKBK 2 with characteristic able to fulfill aspects of indicators of creative thinkng fluency and flexibility. SK2 belong to TKBK 1 with characteristic able to fulfill aspects of indicators of creative thinking fluency. SK3 belong to TKBK 1 with characteristic able to fulfill aspects of indicators of creative thinking fluency. SK4 belong to TKBK 2 with characteristic able to fulfill aspects of indicators of creative thinkng fluency and flexibility. SK5 belong to TKBK 1 with characteristic able to fulfill aspects of indicators of creative thinking fluency. SK6 belong to TKBK 0 with characteristic of not able meet the four aspects of the indicator of creative thinking. Keywords: Creative Thingking, Math Skill, Fluency, Flexibility, Originality,Elaboration